Revolutionizing Quranic Education for 4th Grade Student Through Customized Open-Source Operating System - Bhamana Apta Reyhandendra; Idris Mustapha Abdullahi; Garba Zakariya’u (The Indonesian Institute of Science and Technology Research, 2023)
This study aims to develop an open-source and legal operating system for Quranic education that can be used for teaching the Quran to 4th-grade students using a computer. The operating system display is customized using code commands and Gnome Tweak Tool, and includes themes, shells, icons, fonts, OS logos, backgrounds, booting screens, and multimedia. The IQROS Linux distribution was designed to assist teachers in teaching Quranic lessons to elementary school students, and was evaluated using a questionnaire at a particular elementary school in Indonesia. The study found that the majority of respondents agreed that the color and background design were appropriate, and the use of IQROS Linux was suitable for facilitating religious learning. The software was found to help teachers with their work and increase student interest in learning the Quran, demonstrating the potential of IQROS Linux to enhance religious education in elementary schools. The relevant future resreach is to conduct a longitudinal study to assess the long-term impact of using IQROS Linux on students' Quranic learning outcomes. This could involve tracking students' progress over several years to measure their retention of Quranic knowledge and their ability to apply it in their daily lives.